Treatment of Chemotherapy-Induced Nausea and Vomiting in Hematological Patients (Universitas Medica, 2021)
Nausea and vomiting (NaV) are two of the adverse effects frequently associatedwith the administration of chemotherapy in addition to other drugs used inhematology. The importance that the prevention and management of thesesymptoms has in our patients, lies in the risks they represent when they are nottreated correctly, such as: dehydration, hydroelectrolytic disorders and acute renalfailure. For the preparation of this article, a review of the literature was carried outbased on the evidence and available schemes for the prevention and treatment ofNV induced by medications used in the management of patients with hematologicalpathologies.